Determination of Ascorbic Acid, Total Phenolic Content and Antioxidant Activities in Turmeric Leaves of Different Maturity Stages - N, Ahmad; F, Ismail; Haiyee Z, Abdul (Malaysian Journal of Science, 2005)
A preliminary study was conducted to evaluate the ascorbic acid, total phenolic and antioxidant activities containing in turmeric leaves at different maturity stage. The total phenolic content, determined according to the Folin-Ciocalteu method was higher (77.4mg/100g) in mature than less mature turmeric leaf (55.2mg/100g). Antioxidant of methanolic extract evaluated according to the ÃŽÂ²-carotene bleaching method expressed as % inhibition relative to control were 81.7% in mature leaf and 13.5% in less mature leaf on dry weight basis. The ascorbic acid content analyzed using Hung & Yen method (2002) varied from 5.09 to 5.60 mg/100g in less mature and mature leaf. Results indicated a correlation between total phenolic content and antioxidant activities and higher amount of ascorbic acid content, total phenolic and antioxidant activities in mature than less mature turmeric leaf.